Analysis of the Impact of Unified E-Bupot on Compliance with Income Tax Article 23 Withholding, Payment, and Reporting at PT Samudera Makassar Logistik - Irwanti, A. Azzahra Asri; Hamzah, Hajrah; Afiah, Nur (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
This study aims to analyze the implementation of the Unification e-Bupot system in the process of withholding, depositing, and reporting Article 23 Income Tax at PT Samudera Makassar Logistik, assess its compliance with applicable tax regulations and procedures, and test the impact of Unification e-Bupot on company compliance in depositing and reporting Article 23 Income Tax. This study uses a qualitative method with a focus on the impact of the implementation of the Unification e-Bupot system on company compliance in fulfilling its tax obligations during the period April 2022 to April 2024. Data were collected through documentation and interviews, then analyzed using four components: data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the Unification e-Bupot system has had a positive impact by simplifying the process of withholding, depositing, and reporting Article 23 Income Tax, and its implementation is in accordance with applicable tax regulations, although there are still delays caused by external factors such as server disruptions. Overall, PT Samudera Makassar Logistik is assessed as a compliant taxpayer based on Norman D. Nowak's compliance theory and the Minister of Finance Regulation Number 39/PMK.03/2018. The implementation of the e-Bupot Unification system has been proven to increase efficiency and compliance in fulfilling tax obligations.